Isolation of a novel strain of Monoraphidium sp. and characterization of its potential for α-linolenic acid and biodiesel production. (November 2018) - Lin, Yimeng; Ge, Jingping; Ling, Hongzhi; Zhang, Yunye; Yan, Xiufeng; Ping, Wenxiang
Highlights: A novel microalgal strain (HDMA-11) was isolated and identified as Monoraphidium sp. HDMA-11 accumulated high lipid content in autotrophic conditions. High n-3 PUFA and ALA content make HDMA-11 suitable as a nutritional supplement. HDMA-11 has the potential to be developed as a source of biodiesel feedstock. Abstract: α-Linolenic acid (ALA) is an essential fatty acid which cannot be synthesized de novo in mammals and must be ingested regularly in the diet. In this study, a microalgal strain named HDMA-11 was isolated from Lake Ming, China, and was found to accumulate a high ALA content (39.2% of total lipids). Phylogenetic neighbor-joining analysis indicated that HDMA-11 belongs to the genus Monoraphidium (Selenastraceae, Sphaeropleales) and its 18S ribosomal DNA sequence seemed to be a new molecular record of a Monoraphidium species. The fatty acid profiles, biomass productivity and lipid content of HDMA-11 were also investigated in autotrophic conditions. The high levels of polyunsaturated fatty acids in HDMA-11, especially ALA, make it suitable as a source of nutritional supplementation for human health. Furthermore, HDMA-11 exhibited good properties for biodiesel production, characterized by high lipid content (28.5% of dry weight), moderate biomass productivity (31.5 mg L −1 day −1 ) and a promising lipid profile.